New mitochondrial genomes of 39 soil dwelling Coleoptera from metagenome sequencing - Andújar, Carmelo (Mitochondrial DNA B Resour, 2019)
High-throughput DNA methods hold great promise for the study of the hyperdiverse arthropod fauna of the soil. We used the mitochondrial metagenomic approach to generate 39 mitochondrial genomes from adult and larval specimens of Coleoptera collected from soil samples. The mitogenomes correspond to species from the families Carabidae (6), Chrysomelidae (1), Curculionidae (9), Dermestidae (1), Elateridae (1), Latridiidae (1), Scarabaeidae (3), Silvanidae (1), Staphylinidae (12), and Tenebrionidae (4). All the mitogenomes followed the putative ancestral gene order for Coleoptera. We provide the first available mitogenome for 30 genera of Coleoptera, including endogean representatives of the genera Torneuma, Coiffaitiella, Otiorhynchus, Oligotyphlopsis, and Typhlocharis.